The smell of other people's houses - Hitchcock, Bonnie-Sue (Wendy Lamb Books, 2016)
"Growing up in Alaska in the 1970s isn't like growing up anywhere else: Don't think life is going to be easy. Know your place. And never talk about yourself. Four vivid voices tell intertwining stories of hardship, tragedy, wild luck, and salvation"--